2020
DOI: 10.15344/2456-8007/2020/147
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Potential Mechanisms of Injury and Treatment Targets in COVID-19, SARS-Cov-2 Infection

Abstract: The severe acute respiratory syndrome coronavirus 2, SARS-CoV-2, is the most serious pandemic in modern times. The disease was first reported in January of 2020 in China’s city of Wuhan, Hubei province, and since then it has spread worldwide. Given the rapid spread of the virus and the burden it has taken on the healthcare systems it has swept through, there is the need for a concise description of current understanding of the pathogenesis of organ failure in SARS-CoV-2 infection while acknowledging that more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Inflammatory infiltrates including an abundance of macrophages and CD4+ T cells have been identified in several autopsy studies. [13] Diagnosis of viral etiology, requires endomyocardial biopsy with histopathologic examination. Identification of the SARS-CoV-2 genome in cardiac tissue or viral particles in cardiomyocytes is also imperative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory infiltrates including an abundance of macrophages and CD4+ T cells have been identified in several autopsy studies. [13] Diagnosis of viral etiology, requires endomyocardial biopsy with histopathologic examination. Identification of the SARS-CoV-2 genome in cardiac tissue or viral particles in cardiomyocytes is also imperative.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] Three months later, the disease rapidly evolved into a global pandemic with putative pathogenetic mechanisms underlying the increased morbidity and mortality include acute inflammation, thrombogenesis, vasoconstriction, hemoglobin dysfunction and T-cell dysregulation [3]. These mechanisms are discussed in details and illustrated in a recently published paper by our group (Zhyvotovska A, Yusupov D et.al) [3] that also outlines some of the likely causes of the cardiac effects of COVID-19 that are, at least in part, due to reduction of angiotensin converting enzyme 2 (ACE2), acute inflammatory responses, hypoxia, and disruptions in the coagulation pathway [3] At present there are 22.6 million confirmed cases of COVID-19 worldwide with nearly 800,000 death attributed to the disease with the majority of documented cases in the United States (5.6 million and 174,000 death). [4] Named according to genomic similarity to the virus responsible for the SARS pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been identified as the causal agent of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first detected case of SARS-CoV-2 in December 2019, the virus has spread at a formidable pace to infect more than 2 million individuals globally, claiming close to 140,000 lives by mid-April 2020. There is a growing body of evidence that suggests that patients with SARS-CoV-2 infection are at increased risk of thrombosis, coagulopathy and thromboembolic events [ 1 ]. A recent study from Netherlands reported a 31% incidence of thrombosis in 184 patients admitted to the ICU [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of this devastating disease is growing exponentially. To date, there is an increasing concern of thrombosis, coagulopathy and thromboembolic events in patients with SARS-CoV-2 infection [ 1 ]. Increased rate of venous thrombosis and acute ischemic cerebrovascular accidents were reported in patients requiring critical care in Netherlands despite at least standard doses of thromboprophylaxis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por lo que se sugiere que esta vía del complemento podría inducir la muerte celular y, por lo tanto, contribuiría al daño renal [19] . Adicionalmente, el daño directo en dichas estructuras celulares podría exacerbar la producción de citoquinas pro-inflamatorias a nivel local; y a su vez, incrementar los niveles de la interleuquina 6 (IL-6) a nivel sistémico [28,29] . En ese sentido, se ha observado que la injuria a las células epiteliales de los túbulos aumenta la expresión de la IL-6 en estudios realizados en humanos y en animales [28] , que los podocitos expresan el receptor de IL-6 (IL-6R) en su membrana y que un proceso inflamatorio como puede ser el encontrado en pacientes con infección por la COVID-19 produce una regulación a la alta de IL-6R [30] .…”
Section: Mecanismos De Injuria Celular Renalunclassified